"Everybody wants a Stanley": self-presentation through consumption of status symbols - Saukkonen, Sofija (2025)
This paper examines the purchasing of status symbols as a conspicuous form of consumer self-presentation. Self-presentation through consumption of status symbols is investigated with a holistic and integrative approach using theories of personal identity, social identity, and impression management. The phenomenon of self-presentation is illustrated through a fad involving the Stanley Quencher cup which exemplifies aforementioned theories in a distinctive manner. Accordingly, the objective of this study is to expand understanding on the motives behind consumers purchasing status symbols. This study utilizes qualitative methodology, with data collected via ten semi-structured thematic interviews. Being both recursive and iterative, an abductive thematic analysis method was deemed the most appropriate approach. The findings demonstrate support for prior literature while offering significant insight into theoretical gaps that emerged in the course of the study. Providing five main theoretical contributions, the results support the premise that status symbols serve as tools for identity signalling, self-categorization and impression management. The data however reveals that the results are not homogenous among the respondents, indicating a clear dichotomy in the consumer base. Both consumer categories partake in status symbol consumption nonetheless for different reasons. Another unforeseen theme that emerges in the findings is the negative emotions associated with consumption of popular status symbols. Findings suggest that the conflicting emotions are connected to the friction between a desire for uniqueness and a desire to belong to the mainstream. Broadening current understanding on the subject, this study offers a variety of practical implications as well as directions for future research.